An updated model using a reflection coefficient for predicting performance of pressure-retarded osmosis - Al-Musawi, Osamah A.H.; Abdul Wahab Mohammad,; Ang, Wei Lun; Hameed B. Mahood,; Abdul Amir H. Kadhum, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mathematical model was used to predict the performance of membrane process. In this study, an updated-mathematical model has been developed to study the forward osmosis (FO) and pressure-retarded osmosis (PRO) processes. This model has been advanced by taking into consideration the reflection coefficient, internal and external concentration polarizations, and structural membrane parameters, as well as the equations of applied pressure and mass transport for feed and draw solutions together. The model was validated through prediction of the water and salt fluxes using the membrane performance data published in other articles. The estimated values of the reflection coefficient ranged from 0.868 to 0.9 for FO and 0.9 to 0.95 for PRO. For this reason, it is not possible to consider the reflection coefficient to be equal to one as normally assumed in membrane modeling study. Other findings have showed that the varying salt fluxes at different concentrations and cross-flow velocities adversely impacted the FO and PRO modules. Internal and external concentration polarizations have been studied and compared with their effect on the effectiveness of the FO/PRO process. The model has demonstrated its ability to predict flux in the PRO greater than FO because of the model primary reliance on the applied pressure to drive the osmotic process. The ratio of must be effectively managed to correspond with operating limits and the value must also be kept to a minimum in order to avert the drastical drop in the flux, the fouling, and the membrane damage.